Influence of weather conditions on productivity fluctuations of potatoes and sugar beet in Republic of Belarus - Davydenko, Olga V.; Lopuch, Piotr S. (Journal of the Belarusian State University. Geography and Geology, 2017)
Dynamics of productivity of potato and sugar beet, a current state and prospects of the relevant branches of plant growing are considered. Delay of growth of productivity of potato and steady positive dynamics of productivity of sugar beet in the territory of Republic of Belarus are revealed. By means of creation of lines of trends economic tendencies are installed in the dynamics of productivity: growth in the 1970–80s years, decrease at the end of the XX century and growth at the beginning of the XXI century. A steady tendency of increase of a role of an agrotechnology in formation of a crop of sugar beet and reservation of a share of the weather making dispersion of productivity of potato at the level of more than 50 % are found. Decrease in dependence of productivity of potato on weather conditions is followed by strengthening of territorial differentiation of this dependence. Weather conditions make the smallest contribution to dispersion of productivity of potatoes in the west and south of the republic, the greatest – in Vitebsk region. It is established that potato growing, in comparison with cultivation of sugar beet, needs implementation of measures for adaptation to the changed climatic conditions and improvement of an agrotechnology for the reserve of the leading positions of Belarus in this branch of plant growing.